Role of organic carbon and nitrogen of mineral waters in their metabolic effects at female rats - Igor L Popovych; Yuriy V Zavidnyuk; Mykhaylo M Korda; Igor R Mysula; Ivan M Klishch; Walery Zukow (Kazimierz Wielki University, 2018)
Background. Organic substances, despite their presence in all drinking mineral waters, are still considered to be active only in the water of Naftussya type (which, due to mineralization less than 1 g/L, are not formally mineral), whereas the physiological activity of true mineral waters (which mineralization is greater than 1-2 g/L) are associated with electrolytes and trace elements. The purpose of this study was to clarify the role of organic carbon and nitrogen of mineral waters in their effects on certain parameters of metabolism. Material and Methods. Experiment was performed on 48 healthy female Wistar rats 240-290 g divided into 5 groups. Animals of the first group for 6 days administered a single tap water through the probe at a dose of 1,5 mL/100 g of body mass. In the second group we administered the water Naftussya from the Truskavets' layer, in the third group the water Sophiya of the Truskavets' field. The rats of the fourth group received the native water from the Gertsa (Bucovyna) field, and the last group its artificial salt analogue. The day after the completion of the drinking course in all rats some metabolic parameters were registered. Results. On the basis of the correlation analysis with step-by-step exclusion, four metabolites of blood as well as five metabolites of urine are included in the regressive model for organic carbon (R=0,697; R2=0,486; Adjusted R2=0,347; F(10,4)=3,5; p=0,0025). Organic nitrogen of mineral waters affects five metabolic parameters of urine only, but with approximately the same force (R=0,621; R2=0,385; Adjusted R2=0,312; F(5,4)=5,3; p=0,0008). Conclusion. Organic substances of mineral waters play an essential role in their effects on the parameters of metabolism.